Assessing Quality of Life in Cypriot Patients with Inflammatory Bowel Disease - Maria Tsoukka; Eleni Jelastopulu; George Charalambous; Panagiota Evangelou (Research Developments in Medicine and Medical Science Vol. 2, 2023)
The study investigated the impact of idiopathic inflammatory bowel disease (IBD) on health-related quality of life (HRQoL) using the Greek Short Inflammatory Bowel Disease Questionnaire. 100 patients with IBD were evaluated. The study found that age, gender, and family status affected HRQoL in patients with UC and CD. Higher HRQoL scores were observed in males, older ages in UC, married in CD, and CD patients treated with biological factors. The study concluded that IBD had a negative impact on HRQoL.